DAMPAK ANGKA PUTUS SEKOLAH TERHADAP DAYA SAING TENAGA KERJA: STUDI KOMPARATIF: 4 NEGARA ASEAN - Ahmad Ruspandi (Jurnal Studi Ekonomi dan Pembangunan, 2026)
This study compares school dropout rates and labor competitiveness in Indonesia, Malaysia, the Philippines, and Thailand using World Bank data (2019–2023). Results show that Indonesia has the highest school completion rate (99.39%) but low labor productivity (USD 26,989), far below Malaysia (USD 64,128) and Thailand (USD 36,919). Malaysia, despite having the lowest completion rate (77.97%), achieves the highest productivity. Indonesia also spends the least on education (1.03% of GDP). The study concludes that low dropout rates alone do not improve labor competitiveness without quality education. It recommends Indonesia shift focus from quantity to quality, align curriculum with industry, and strengthen vocational training.